PROMOSI PARIWISATA MALUKU MELALUI AJANG PEMILIHAN PUTRI PARIWISATA - Tamaneha , Trivena Sephani; Pesulima, Merry; Pakniany, Yamres (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2023)
Promotion of Maluku Tourism Through the Miss Tourism Selection Event is carried out because this event shows activities aimed at promoting tourism. However, after the selection of miss tourism, it can be seen from the contribution of the duties and responsibilities of a tourism princess that it is still ineffective in promoting tourism. Based on this, the authors conducted research to formulate the problem; (1). How to promote Maluku tourism through the Miss Tourism Maluku selection event; (2). How was the performance of Miss Tourism after participating in the Miss Maluku Tourism and Miss National Tourism selection events? This study used a qualitative method, with data collection techniques in the form of interviews conducted with several informants from both tourism women and government elements, in this case, the Maluku Provincial Tourism Office. The results of the study show that there are still many programs from the daughters of tourism that cannot be carried out in the field effectively because they are hindered by several obstacles, for example, lack of funds, lack of coordination, and not yet facilitated by the government. Therefore the author provides a solution that utilizes this event as a forum for promoting Maluku tourism. The author suggests collaborating on Penta helix tourism with elements consisting of government, academia, business, community, and media.